Why Am I stressed out?: Neglecting the internal stressors among undergraduate students in Malaysia - Toh, Seong-Yuen *; Kaur, Ranita *; Tehseen, Shehnaz * (Common Ground Research Networks, 2021)
Stress among undergraduate students in Malaysia is a growing concern. However, policy makers mostly account for external stressors in decision making. For instance, most of the stress-coping mechanisms in private universities focus predominantly on external stressors. Internal stressors, like differences in personality traits of students, are overlooked when determining preventive measures adopted by private universities to cope with students’ mental health. This study investigates whether internal stressors make some students more susceptible to stress than others. The relationships between personality traits and stress among undergraduate students in Malaysia and the concept of brooding are of particular interest. Data from 131 respondents were analyzed using SPSS and Smart-PLS software reveal that the model in this study has large predictive power (R 2= 0.487) with Neuroticism (large effect size) and Agreeableness (small effect size) as predictors of student stress. Furthermore, brooding (low Extraversion, high Neuroticism, and high Consciousness) is statistically the strongest predictor. Finally, female students are found to be more susceptible to stress. The findings support the claim that policy makers should reconsider internal stressors in treatment-matching of high-risk category of undergraduate students in Malaysia.